Pre-clinical safety and efficacy evaluation of Helicobacter Pylori neutrophil-activating protein (NAP)-armed CAR-T cells targeting B cell lymphomas - Jing Ma; Tina Sarén; Chuan Jin; Hyeong Su Kim; Paola Donaji Contreras Pineda; Marina de Bernard; Rose-Marie Amini; Veronica Rondahl; Gunilla Enblad; Di Yu; Magnus Essand (Cancer Immunology, Immunotherapy)
Abstract CD19 CAR-T cell therapy shows striking results in treating B cell malignancies. However, approximately two-thirds of the lymphoma patients eventually relapse, with about one-third displaying CD19-negative tumors at relapse. Our previous study showed that CAR-T cells armed with the Helicobacter pylori neutrophil-activating protein (NAP), CAR(NAP)-T cells, can trigger a bystander immune response and eliminate CAR-target-antigen-negative tumor cells. Here, we report the development of CD20-targeted CAR-T cells (CAR20-T cells), with the targeting moiety from rituximab, and the safety and efficacy of NAP-armed CAR-T cells. CAR20-T cells displayed efficient and specific cytotoxic potential against multiple human B cell lymphoma cell lines in vitro. In addition, primary mantle cell lymphoma cells, isolated from a patient who relapsed after rituximab treatment, can also be eliminated by CAR20-T cells. CAR20(NAP)-T cells delayed tumor growth and prolonged survival of mice with lymphoma. No obvious histopathological alteration in major organs were observed in mice treated with CAR(NAP)-T cells. Further, no excessive cytokine release or immune cell activation was observed when human blood from healthy volunteers was exposed to recombinant NAP protein in an ex vivo blood loop assay, suggesting a safe therapeutic profile for NAP. Taken together, these results warrant the clinical investigation of CAR20(NAP)-T cells.